PENGARUH FAKTOR INTERNAL BANK TERHADAP VOLUME KREDIT PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2015)
This research is research that examines the effect of the internal factors of the volume of bank credit to commercial banks registered in Bank Indonesia. In this study, researchers used a purposive sampling. The data analysis technique used is multiple linear regression. Based testing can be concluded that: (1) ROA significant positive effect on bank lending to commercial banks in Indonesia. (2) CAR no significant positive effect on bank lending (3) NPL no significant positive effect on bank lending. (4) BOPO significant negative effect on bank lending.Keywords: ROA, CAR, NPLs, ROA, Distribution of Credit